2020
DOI: 10.1074/jbc.ra120.014103
|View full text |Cite
|
Sign up to set email alerts
|

Engineered anti-inflammatory peptides inspired by mapping an evasin–chemokine interaction

Abstract: Chemokines mediate leucocyte migration and homeostasis, and are key targets in inflammatory diseases including atherosclerosis, cytokine storm and chronic auto-immune disease. Chemokine redundancy and ensuing network robustness has frustrated therapeutic development. Salivary evasins from ticks bind multiple chemokines overcoming redundancy, and are effective in several pre-clinical disease models. Their clinical development has not progressed due to concerns regarding potential immunogenicity, parenteral deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…Furthermore, the linear peptide Ev4 Glu 14 –Asn 31 , derived from the Evasin-4 sequence, possesses nanomolar affinity to CCL5 on its own. Similar tight affinities have recently been shown for peptides derived from the N terminus of P672 and are potent binders of CCL8 ( 31 ). The N-terminal region of Evasin-4 embodies multiple tyrosines, which are proposed to mimic an N-terminal region of CC-chemokine receptors ( 32 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the linear peptide Ev4 Glu 14 –Asn 31 , derived from the Evasin-4 sequence, possesses nanomolar affinity to CCL5 on its own. Similar tight affinities have recently been shown for peptides derived from the N terminus of P672 and are potent binders of CCL8 ( 31 ). The N-terminal region of Evasin-4 embodies multiple tyrosines, which are proposed to mimic an N-terminal region of CC-chemokine receptors ( 32 ).…”
Section: Discussionsupporting
confidence: 80%
“…Development of chemokine-binding peptides and peptidomimetics based on Evasins may provide more perspectives ( 34 ). Recently, several peptides derived from C8-Evasin P672 were shown to effectively block inflammation because of binding to multiple CC-type chemokines ( 31 ). Ev4 Glu 14 –Asn 31 effectively inhibits CCL5-induced monocyte migration.…”
Section: Discussionmentioning
confidence: 99%
“…Although EVA-1 and EVA-4 have effectively diminished inflammation in the murine model of acute lung injury and myocardial infarction, respectively ( Russo et al., 2011 ; Braunersreuther et al., 2013 ), their application as drugs could be challenging due to the complex structures and difficult production (personal observation). However, it has recently been shown that short linear and cyclic peptides derived from the N -termini of EVA-P672 and EVA-4 retain binding and inhibitory activity comparable to full-length parent proteins ( Darlot et al., 2020 ; Denisov et al., 2020b ). Moreover, these peptides could be further modified and adjusted for neutralization of chemokines of interest.…”
Section: Evasinsmentioning
confidence: 99%
“…Due to its broad CC chemokine-binding spectrum, Evasin-4 is considered the most suitable candidate for therapeutic development (86). More recently, Evasin-inspired artificial peptides dramatically reduced inflammation in vivo by targeting multiple chemokines (87). These peptides might therefore provide a route to the development of new anti-inflammatory therapeutics for chronic autoimmune diseases such as rheumatoid arthritis and inflammatory diseases such as atherosclerosis.…”
Section: Recruitment Of Blood-borne Innate Immune Cellsmentioning
confidence: 99%
“…These peptides might therefore provide a route to the development of new anti-inflammatory therapeutics for chronic autoimmune diseases such as rheumatoid arthritis and inflammatory diseases such as atherosclerosis. Moreover, the mechanism of action of these peptides suggests that they might also be useful in acute infectious diseases such as influenza or COVID-19, where exuberant cytokine responses are thought to be at least partially responsible for tissue injury (87).…”
Section: Recruitment Of Blood-borne Innate Immune Cellsmentioning
confidence: 99%